A two-stage pretreatment using dilute sodium hydroxide solution followed by an ionic liquid at low temperatures: Toward construction of lignin-first biomass pretreatment. (September 2019) - Yang, Mingkun; Zhang, Xin; Cheng, Gang
Abstract: A two-stage pretreatment process is constructed to test the feasibility of lignin-first biomass pretreatment. It is expected that mild pretreatment conditions help to reduce structural alterations to lignin or minimize condensation reactions in lignin which are important for certain high value applications. The pretreatment process consists of a step using 1% sodium hydroxide solution to increase the porosity of biomass and a second step using a typical ionic liquid, 1-ethy-3-methylimidazolium acetate ([C2 C1 Im][OAc]), to transform native crystalline cellulose into amorphous cellulose and therefore enhance enzymatic hydrolysis efficiency. Both pretreatments are carried out at 60 °C for 3 h to lower the severity of the pretreatment. Lignin samples extracted from untreated biomass (Lignin 1), liquid phase after NaOH pretreatment (lignin 2), liquid phase after subsequent IL pretreatment (lignin 3) and the lignin remaining in pretreated biomass (lignin 4) were analyzed using FTIR and by measuring molecular weight and antioxidant properties. Graphical abstract: Unlabelled Image Highlights: Lignin-first biomass pretreatment was tested. NaOH pretreatment at 60 °C increases porosity of biomass. Ionic liquid transformed native cellulose into amorphous at 60 °C. Lignin structure was controlled by pretreatment severity.